Analysis of Santriwati’s Character Building in Miftahul Ulum Islamic Boarding School Sipring Pagelaran Based on 18 Character - Hanif Maulaniam Sholah; Mawaddah Mawaddah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2023)
The Objective of this study was describe kind of santri’s character in Boarding Islamic School Miftahul Ulum based on 18 Characters. This research used a Qualitative research. The technique of collecting data was observation, interview and documentation. The object of this research is Santriwati’s Miftahul Ulum. The findings of this research are as follow: Miftahul Ulum Islamic Boarding School applies eleven characteristics that shape the character of santriwati, such as religious, honest, social care, discipline, responsible, tolerance, smart, hard work, friendly, spirit, love to read. These eleven characters are very helpful in the process of forming the characters santiwati. Because of this, the ustadzah familiarizes santriwati with various activities related to these characters. There are some santriwati characters who do not enter 18 character namely smart and spirit. And there are also some characters of the santriwati found in character 18 but are not found in the character of santriwati. They are democratic, creative, independent, love peace, curiosity, spirit of nationality, value attainment, caring for the environment and love country.